Cell‐Cycle‐Dependent Regulation of Cell Adhesions: Adhering to the Schedule: Three papers reveal unexpected properties of adhesion structures as cells progress through the cell cycle. (28th November 2018) - Li, Yitong; Burridge, Keith
Abstract : Focal adhesions disassemble during mitosis, but surprisingly little is known about how these structures respond to other phases of the cell cycle. Three recent papers reveal unexpected results as they examine adhesions through the cell cycle. A biphasic response is detected where focal adhesions grow during S phase before disassembly begins early in G2. In M phase, activated integrins at the tips of retraction fibers anchor mitotic cells, but these adhesions lack the defining components of focal adhesions, such as talin, paxillin, and zyxin. Re‐examining cell‐matrix adhesion reveals reticular adhesions, a new class of adhesion. These αVβ5 integrin‐mediated adhesions also lack conventional focal adhesion components and anchor mitotic cells to the extracellular matrix. As reviewed here, these studies present insight into how adhesion complexes vary through the cell cycle, and how unconventional adhesions maintain attachment during mitosis while providing spatial memory to guide daughter cell re‐spreading after cell division. Abstract : Cell‐ECM adhesion changes biphasically as cells progress from G1 to S to G2. In mitosis, focal adhesions are replaced by αVβ5 integrin‐mediated reticular adhesions at the tips of retraction fibers.